NMR studies of methane and hydrogen in microporous materials: Пористые и низкоразмерные структуры - Ji, Yu; Hamida, J.A.; Tang, Yibing; Sullivan, N.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
We review the results of nuclear magnetic resonance studies of the molecular dynamics of the quantum gases HD and CH4 adsorbed in the cages of microporous structures. Measurements of the variation of the nuclear spin-lattice and nuclear spin-spin relaxation times with temperature provide detailed information about the translational and rotational dynamics of the adsorbed molecules over a wide temperature range.